Bacillus subtilis na qualidade dos pintinhos ao nascer, desempenho e características intestinais dos frangos - Borges, Liliana Longo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
A study was conducted to verify the effect of in ovo inoculation of Bacillus subtilis and feed supplementation during the creation, on the morphological and morphometric characteristics of the small intestine, performance and carcass yield of broilers. The study consisted of two experiments. In the first 500 fertile chicken eggs over five horizontal incubators were used. The experimental design was randomized blocks, each considered as a block incubator, with five treatments (control, NaCl, CFU 106, CFU 107, CFU 108), and 100 eggs/treatment. At 18 days of incubation the eggs were inoculated with the solutions in the air cell and the hatch were evaluated for quantification and identification of Bacillus subtilis in the intestinal mucosa, hatchability of fertile eggs, total rate of hatching, embryo mortality and chick quality, birth weight and weights of the intestine, liver and yolk sac of male chicks. The concentration 107 provided better results relative to hatchability and chick weight at birth. In the second experiment in 2700 fertile eggs were incubated in an incubator CASP single stage. At 18 days of incubation 1350 eggs were inoculated with 107 CFU Bacillus and 1350 eggs remained without inoculation. When the hatch in the shed males were housed according to the treatment. The design was a randomized block design with a 2x2 factorial design (in ovo inoculation of Bacillus subtilis or not X supplementation of Bacillus subtilis in the creation phase or not), with six replicates of 35 birds each, totaling 840 birds. Were analyzed the morphometry of the small intestine, the weights of the liver, intestine and pancreas at one, four, eight, 13, 20 and 41 days of age, the results at 21 and 42 days of age, performance at 21 and 42 days of age, carcass yield and cuts, and meat quality at 42 days of age. The in ovo inoculation of Bacillus subtilis and feed supplementation promoted best results for depths length of villi and crypts in ...

Foi realizado um estudo para verificar o efeito da inoculação in ovo de Bacillus subtilis e sua suplementação na ração durante a fase de criação, sobre as características morfológicas e morfométricas do intestino delgado, desempenho e rendimento de carcaça de frangos de corte. O estudo foi composto por dois experimentos. No primeiro foram utilizados 500 ovos férteis de frango distribuídos em cinco incubadoras horizontais. O delineamento utilizado foi em blocos casualizados, sendo cada incubadora considerada um bloco, com cinco tratamentos (Controle, NaCl, 106 UFC, 107 UFC, 108 UFC), e 100 ovos/tratamento. Aos 18 dias de incubação os ovos foram inoculados com as soluções na câmara de ar e ao eclodirem foram avaliados à quantificação e identificação de Bacillus subtilis na mucosa intestinal, taxa de eclosão de ovos de matrizes pesadas, taxa de eclosão total, mortalidade embrionária, qualidade dos pintinhos, peso ao nascer e pesos do intestino, fígado e saco de vitelo dos pintinhos machos. No segundo experimento foram incubados 2700 ovos férteis em uma incubadora CASP de estágio único. Aos 18 dias de incubação 1350 ovos foram inoculados com 107 UFC Bacillus subtilis e 1350 ovos permaneceram sem inoculação. Ao eclodirem os machos foram alojados no galpão de acordo com os tratamentos. O delineamento utilizado foi em blocos casualizados com esquema fatorial 2x2 (inoculação in ovo de Bacillus subtilis X suplementação de Bacillus subtilis na ração), com seis repetições com 35 aves cada, totalizando 840 aves. Foram analisados a morfometria do intestino delgado, os pesos do fígado, intestino e pâncreas aos um, quatro, oito, 13, 20 e 41 dias de idade, o desempenho aos 21 e 42 dias de idade, o rendimento de carcaça e cortes, e a qualidade da carne aos 42 dias de idade. A inoculação in ovo e a suplementação de Bacillus subtilis na ração promoveram melhores resultados para altura das vilosidades e ...
Keywords: Frango de corte - Nutrição; Rações - Aditivos; Suplementos dieteticos; Microbiota; Mucosa intestinal; Probióticos; Probiotics